2015
DOI: 10.12657/denbio.073.010
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of iron-binding compounds in root of Pinus sylvestris challenged by Heterobasidion annosum sensu lato

Abstract: Abstract:We examined the interaction between the roots of Pinus sylvestris and closely related species Heterobasidion annousum s.l. (H. annosum s.s., H. parviporum, H. abietinum) that differ in host plant preference. The aim of the current study was to determine in roots the accumulation pattern of low molecular mass compounds such as catecholate and hydroxamate derivates, oxalic acid as well as iron-reduction ability of that low molecular mass compounds, that play important roles in wood degradation and they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…used in the current study. In addition, levels of oxalic acid were correlated negatively with cell death (Mucha et al 2015). This may suggest that oxalic acid is used as a source of H 2 O 2 , since oxalic acid is a substrate for oxalate oxidase, which releases H 2 O 2 and CO 2 from oxalic acid (Zhang et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…used in the current study. In addition, levels of oxalic acid were correlated negatively with cell death (Mucha et al 2015). This may suggest that oxalic acid is used as a source of H 2 O 2 , since oxalic acid is a substrate for oxalate oxidase, which releases H 2 O 2 and CO 2 from oxalic acid (Zhang et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that iron plays a role in fungal-host interactions in both leaves [1,2,3] and roots [4,5,6,7,8]. Thus, metal-binding siderophores secreted by fungi, which regulate iron distribution, play an important role in virulence [1,3,5] and in maintaining the mutualistic interaction of mycorrhizae [9].…”
Section: Introductionmentioning
confidence: 99%